Increased synthesis of a coenzyme linked to longevity can combat disease. (15th November 2018) - Parikh, Samir M.
The coenzyme NAD+ can be produced from the amino acid tryptophan. It emerges that inhibiting an enzyme that degrades an intermediate in this pathway can help to combat kidney and liver diseases in mouse models. Increased NAD+ synthesis protects mice against liver and kidney diseases.